Função afim: uma sequência didática envolvendo atividades com o geogebra - Scano, Fabio Correa (2009)
In the preliminary studies held, mainly, in the bibliographic review, it was observed that many essays show learning difficulties that students from different levels of education have regarding the study of the affine function. Wanting to broaden the studies held before to this respect and aware that the theme still needs research, it was considered by hypothesis for this study that a teaching sequence conceived to the light of the Theory of Didactic Situations and to the Theory of Semiotics Representation Registers, mediated by the use of a software of dynamic geometry, the Geogebra, it might contribute for an indication to the study of the affine function. The purpose of this research was to develop a teaching sequence to start the study with 9th graders that contributed to the development of the capability of expressing algebraically and graphically the dependence of the two variants from an affine function and acknowledge that its graphical representation is a straight line, relating the coefficients from the straight line equation with the graphic. After the elaboration, the a priori analysis of the sequence and the application in the 9th grade of a private school from the Great São Paulo, the a posteriori analysis showed that our hypothesis was confirmed, this means, that a sequence developed and applied based on the Theory of Didactic Situations and on the register change of the representation leads 9th graders to acknowledge that the graphic of an affine function is a straight line and the majority to express algebraically and graphically the relation between the two variants of an affine function, besides relating the straight line equation coefficients to the graphical representation of the affine function